2005
DOI: 10.1021/jp050943o
|View full text |Cite
|
Sign up to set email alerts
|

When Light Falls in LOV:  A Quantum Mechanical/Molecular Mechanical Study of Photoexcitation in Phot-LOV1 of Chlamydomonas reinhardtii

Abstract: Plants use sophisticated photosensing mechanisms to maximize their utilization of the available sunlight and to control developmental processes. The plant blue-light receptors of the phot family mediate plant phototropism and contain two light, oxygen, and voltage (LOV) sensitive domains as photoactive elements. Here, we report combined quantum mechanical/molecular mechanical simulations of the photocycle of a complete Phot-LOV1 domain from C. reinhardtii. We have investigated the electronic properties and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
81
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 45 publications
13
81
0
Order By: Relevance
“…They deduced from their calculation results that the reaction pathway proceeds via the triplet T1-state of the FMN, and that the process of adduct formation involves intermediate radicals rather than ionic species. Dittrich et al [30] studied the early steps of the photocycle by performing combined quantum mechanical/molecular mechanical (QM/MM) simulations of a complete LOV1-domain from C. reinhardtii. They investigated the electronic properties and initial structural changes that follow blue-light absorption, and concluded from their calculation results that the pathway for cysteinyl-FMN(CFN) adduct formation proceeds via a neutral radical state, generated by H-atom transfer from the reactive Cys57-residue to the FMN-chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…They deduced from their calculation results that the reaction pathway proceeds via the triplet T1-state of the FMN, and that the process of adduct formation involves intermediate radicals rather than ionic species. Dittrich et al [30] studied the early steps of the photocycle by performing combined quantum mechanical/molecular mechanical (QM/MM) simulations of a complete LOV1-domain from C. reinhardtii. They investigated the electronic properties and initial structural changes that follow blue-light absorption, and concluded from their calculation results that the pathway for cysteinyl-FMN(CFN) adduct formation proceeds via a neutral radical state, generated by H-atom transfer from the reactive Cys57-residue to the FMN-chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has subsequently been investigated in more detail in a series of theoretical studies. Dittrich et al [20] performed quantum chemical calculations for the first excited triplet state of the FMN-related model compound lumiflavin at the ROHF/6-31G(2d,2p) level of theory and concluded from analyzing the resulting Mulliken spin populations that a significant fraction of unpaired spin density is localized on the C4a as well as the C8 position of lumiflavin. Salzmann et al [76,77] demonstrated that not only the ordering of low-lying potential energy hypersurfaces but also the mechanism of triplet generation in the case of FMN-related compounds significantly depends on the environment.…”
Section: Resultsmentioning
confidence: 99%
“…They deduced from their calculation results that the reaction pathway takes place via the triplet T1-state of the FMN and that the process of adduct formation involves rather intermediate radicals instead of ionic species. Dittrich et al [20] studied the early steps of the photocycle by performing combined quantum mechanical/molecular mechanical (QM/ MM) simulations of a complete LOV1 domain from C. reinhardtii. They investigated the electronic properties and initial structural changes that follow blue-light absorption and concluded from their calculation results that the pathway for cysteinyl-FMN adduct formation proceeds via a neutral radical state generated by H atom transfer from the reactive Cys57 residue to the FMN chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…These receptors mediate plant phototropism and contain two light, oxygen, and voltage (LOV)-sensitive domains as photoactive elements. The Phot-LOV1 domain from Chlamidomonas reinhardtii was studied [160]. The electronic properties and structural changes that follow blue-light absorption were studied by combined QM/MM simulations of the photocycle of the Phjt-LOV1 domain of C. reinhardtii [160].…”
Section: The Pigments Cofactors and So Onmentioning
confidence: 99%
“…The Phot-LOV1 domain from Chlamidomonas reinhardtii was studied [160]. The electronic properties and structural changes that follow blue-light absorption were studied by combined QM/MM simulations of the photocycle of the Phjt-LOV1 domain of C. reinhardtii [160]. This allowed one to resolve the structural changes and study the electronic processes accompanying flavin-cysteinyl adduct formation.…”
Section: The Pigments Cofactors and So Onmentioning
confidence: 99%